Building National Defense Awareness in Primary Schools National Development through Citizenship Education: Challenges and Opportunities in the Era of Globalization - Siregar, Delisma; Manihuruk, Waldio; Sari, Kartika; Yunita, Sri; Ndona, Jacobus (Budapest International Research and Critics University, 2024)
Globalization has become a phenomenon that dominates the world today, bringing significant changes in various aspects of social, economic and political life throughout the world. One of the impacts that was felt was a shift in awareness of defending the country among the younger generation, including students at the National Development Elementary School. In this study, we explore the influence of globalization on national defense awareness and the role of students in building it. The methodology used in this study is descriptive qualitative, which involves in-depth analysis of the observed phenomena. Through a literature review, we investigate various perspectives on the impact of globalization on national defense awareness, including changes in national values and identity, dependence on other countries, the influence of media and technology, changes in consumption patterns, and challenges to state sovereignty. The results of the analysis show that globalization has complex and varied impacts depending on a country's political, social and cultural context. In the midst of these changes, the citizenship education paradigm in elementary schools plays an important role in building a strong awareness of defending the country. Civic education not only focuses on teaching state doctrine, but also promotes critical, analytical thinking, and a deep understanding of civic values that go beyond the boundaries of doctrine. Students, as potential agents of change in society, have a key role in building awareness of defending the country. Through education, active participation and use of technology, they can become a driving force in strengthening awareness of defending the country amidst the challenges of globalization. Students' contributions are not only limited to the use of weapons, but also through dedication in their profession and active participation in citizenship education. This research underlines the importance of understanding the impact of globalization, updating the paradigm of citizenship education, and empowering students' role in building a strong and relevant national defense awareness in globalization era.